Kotagede heritage city: Identification of conservation and preservation based on community perspective - Erda Rindasih; Muhammad Izzudin; Muhammad Baiquni (Universitas Merdeka Malang, 2022)
Kotagede is one of the tourism destinations that has been associated with several sites such as education, history, and culture. On the macro and local levels, policies must guarantee that tourism development does not compromise cultural heritage assets that can provide economic, social, and environmental advantages. The aim of the article is to provide an overview of the stakeholders who contributed to the administration and development of the Kotagede tourist conservation and preservation program, focusing on the United Nations World Tourism Organization (UNWTO) standard as a performance indicator. The technique and methods used in this study are observation, filed survey and in-depth interview. The findings indicated that Kotagede had a competitive advantage as a potential tourism destination due to its cultural, historical, gastronomic, architectural, and transportation advantages. The institutional community has been engaged in preserving old structures, promoting tourism, and fostering local economic growth.